METHODOLOGY OF INCREASING QUALITY OF ELECTRICITY IN COMPANIES AND DISTRIBUTION ELECTRICAL NETWORKS - T. A. Ismailov; R. K. Gereykhanov; A. M. Magomedov (Вестник Дагестанского государственного технического университета: Технические науки)
In this article methodologies of increasing quality of electricity are discussed. Analyses of different methodologies were made and new ways to compensate reactive power in companies were proposed.